Organic-inorganic hybrid materials containing metals and lignin, processes for preparing same, and uses thereof

JP7633809B2Active Publication Date: 2025-02-20UPM KYMMENE OYJ +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020570806
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-06-29
Filing Date
2019-06-14
Publication Date
2025-02-20
Estimated Expiration
2039-06-14

Smart Images

  • Figure 0007633809000029
    Figure 0007633809000029
  • Figure 0007633809000030
    Figure 0007633809000030
  • Figure 0007633809000031
    Figure 0007633809000031
Patent Text Reader

Abstract

Organic-inorganic hybrid materials comprising metal compounds and lignin fractions, as well as processes for preparing them, and their use as antimicrobial agents in agriculture and in the human and animal food industries are disclosed.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an organic-inorganic hybrid material comprising a metal compound and a lignin fraction, as well as a process for its preparation and use as an antimicrobial agent in agriculture and in the human and animal food industry. [Background technology]

[0002] In some industries, such as the food industry, bacterial growth must be avoided in order to maintain the hygiene of the products, such as food products, that are processed into the industry. On farms and in slaughterhouses, bacterial growth is on the one hand very common and on the other hand very important to limit and avoid such growth.

[0003] Known products are often ineffective against multiple harmful or pathogenic microorganisms, therefore many different products must be used simultaneously, and known products are often polluting to both the environment and the products in which they are used.

[0004] In these cases, the commonly used products are antibiotics. However, overuse and misuse of these drugs, as well as a lack of new drug development by the pharmaceutical industry due to reduced economic incentives and challenging regulatory demands, are believed to be at the root of the antibiotic resistance crisis.

[0005] Antimicrobial resistance (AMR) is the ability of microorganisms to resist the effects of drugs previously used to treat them. The term includes the more specific "antibiotic resistance," which applies only to bacteria that become resistant to antibiotics. Resistant microorganisms are more difficult to treat and require alternative drugs or higher doses, both of which can be more expensive or more toxic.

[0006] The World Health Organization has affirmed that the inappropriate use of antibiotics in livestock farming is an underlying factor in the emergence and spread of antibiotic-resistant bacteria, and that the use of antibiotics as growth promoters in animal feed should be restricted. The World Organisation for Animal Health has added a set of guidelines to its members to monitor the amount of antibiotics used in livestock farming, recommending the creation and harmonization of an international antimicrobial resistance surveillance and monitoring programme, and ensure the appropriate and prudent use of antibiotics. Another guideline is to implement methodologies that help establish associated risk factors and assess the risk of antibiotic resistance.

[0007] In this regard, products used in agriculture for crop protection and promotion, especially those used to prevent or treat crop infections caused by bacteria, fungi or viruses, also play a substantial role in the quality of human and animal diets.

[0008] It is therefore felt that there is a need to effectively combat these harmful and pathogenic microorganisms, thus avoiding the use of antibiotics and at the same time protecting human and animal health, crops and the environment. Summary of the Invention [Means for solving the problem]

[0009] The above object has been achieved by an organic-inorganic hybrid material comprising a metal compound and a lignin fraction, as claimed in claim 1.

[0010] In another aspect, the present invention relates to a process for preparing said organic-inorganic hybrid material.

[0011] In a further aspect, the present invention relates to the use of said organic-inorganic hybrid material as an antimicrobial agent in agriculture.

[0012] In an additional aspect, the invention relates to an agrochemical product comprising the organic-inorganic hybrid material and an agrochemical additive.

[0013] In a further aspect, the present invention relates to the use of said organic-inorganic hybrid materials as antimicrobial agents in human and animal diets.

[0014] In an additional aspect, the present invention relates to a food product comprising the organic-inorganic hybrid material and a suitable food ingredient.

[0015] In another aspect, the present invention relates to a food supplement comprising the organic-inorganic hybrid material and a suitable food carrier. [Brief description of the drawings]

[0016] Features and advantages of the present invention will become apparent from the following detailed description, from the examples given by way of example, and from the accompanying drawings, in which: [Figure 1] FIG. 1 shows XRPD plots of HMW-Cu with different copper contents, as per Example 3. [Diagram 2] FIG. 1 shows matching overlap between XRPD plots of HMW-Cu 42% and Brochantite (thin lines, from the Mineral Database), as per Example 3. [Diagram 3] FIG. 1 shows ESEM images of HMW-Cu 42% granules as per Example 3 at scale units of 20 μm (a) and 10 μm (a). [Figure 4] FIG. 1 shows EDX analysis of HMW-Cu 17% at one location of a granule, as per example 3. [Diagram 5]FIG. 1 shows TEM images in bright field mode (A) and STEM mode (B) of HMW-Cu 14%, as per Example 3, with a scale unit of 100 nm (left) to 50 nm (right). [Figure 6] FIG. 1 shows TEM images in bright field mode (A) and STEM mode (B) of HMW-Cu 2%, with a scale unit of 200 nm (left) to 20 nm (right), as per Example 3. [Figure 7] FIG. 1 shows XRPD plots of HMW-Cu 17% and MMW-Cu 18%, as per Example 4. [Figure 8] FIG. 1 shows ESEM images of MMW-Cu 18% as per Example 4, with scale units from 100 μm (a) to 1 μm (b). [Figure 9] FIG. 1 shows EDX analysis of HMW-Cu 17% at one location of a granule, as per example 4. [Figure 10] FIG. 1 shows crystals of brochantite in MMW-Cu 14%, as per Example 4. [Figure 11] FIG. 1 shows a STEM image of brochantite crystals embedded in a MMW matrix (MMW-Cu 14%) with selected area X-ray microanalysis as per Example 4. [Figure 12] FIG. 1 shows a STEM image of crystals of brochanite (white) in MMW-Cu 14%, as per Example 4. [Figure 13] FIG. 1 shows XRPD plots of HMW-Cu 11% and HMW-Cu 20% obtained from Cu(NO3)2·3H2O as per Example 5. [Figure 14] FIG. 6 shows the XRPD trace of HMW-Cu 20% obtained by using mechanochemical technique, as per Example 6A. [Figure 15] FIG. 1 shows the XRPD trace of MMW-Cu 21% obtained by using mechanochemical techniques, as per Example 7. [Figure 16]FIG. 1 shows an XRPD trace of HMW-Fe 20%, as per Example 8. [Figure 17] FIG. 13 shows matching overlap between XRPD plots (thin lines, from database) of MMW-Fe 20%, goethite, and lepidocrocite, as per Example 8. [Figure 18] FIG. 1 shows an XRPD plot of the product HMW-Cu obtained in aqueous medium after reaction with 10% copper for 2 hours as per Example 9, the red trace is brochanite. [Figure 19] FIG. 1 shows a) Selected area electron diffraction (SAED) collected on a 200 nm area, and b) and c) STEM images for HMW-Cu 10%, 2 hours, as per Example 9. [Figure 20] FIG. 1 shows the XRPD plot of the product HMW-Cu obtained under mechanochemical wet conditions using Ca(OH)2 as base. The red trace is brochanite. [Figure 21] FIG. 1 shows the efficacy of two samples of HMW-Cu 10 in controlling bacterial infection caused by Rhizoctonia solani on greenhouse grown tomatoes in comparison with a commercial Cu-based product, i.e. Coprantol®, as per Example 11. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The subject of the present invention is therefore an organic-inorganic hybrid material comprising a metal compound and a lignin fraction, in which: the metal compound is selected from metal hydroxides, metal oxides, metal halides, metal sulfates, metal nitrates, metal gluconates, metal oxychlorides, metal acetates, metal carbonates, metal silicates, metal aluminosilicates, and combinations thereof, and the metal is selected from Li, Na, K, Be, Mg, Ca, Sr, Ba, Ti, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ag, Au, Al, Bi, As, and mixtures thereof; - the lignin fraction comprises fragments having a weight average molecular weight of up to 10,000 Daltons as measured by size exclusion chromatography, the fragments comprising, by weight average, up to 55 phenylpropane units; and wherein the metal compound is embedded in the lignin fraction in an amount of up to 50 wt % based on the weight of the organic-inorganic hybrid material.

[0018] The term "organic-inorganic hybrid material" refers to a composite material that includes an inorganic material and an organic polymer. In this case, the metal compound represents the inorganic metal and the lignin fraction represents the organic polymer.

[0019] In a preferred embodiment, in said organic-inorganic hybrid material, the inorganic material is embedded in an organic polymer; more preferably, the inorganic material is scaffolded on the organic polymer.

[0020] Preferably, the metal is selected from Mg, Ca, Ti, Fe, Mn, Co, Ni, Cu, Zn, Ag, Al, and mixtures thereof.

[0021] In a preferred embodiment, the metal comprises Cu, Fe, or a mixture thereof.

[0022] In a more preferred embodiment, the metal compound comprises brochanite, gerhardite, goethite, tridymite, or mixtures thereof.

[0023] In a most preferred embodiment, the metal compound comprises brochantite.

[0024] Brochantite is a sulfate mineral with the chemical formula Cu4SO4(OH)6.

[0025] Lignin is a class of complex organic polymers that form the important structural material in some algae, vascular plants, including their bark, and in the supporting tissues of herbaceous plants, such as wood (i.e., softwoods and hardwoods), straw of all cereals, sugarcane bagasse, grasses, flax, jute, hemp, or cotton, etc. Lignin can also have mineral sources, such as peat, leonardite, and coal.

[0026] Chemically, in its native form, lignin is a highly irregular, randomly cross-linked polymer of phenylpropane units linked by many different bonds, with a weight average molecular weight of over 20,000 Daltons. A representative and exemplary lignin fragment (I) containing the most important bond patterns is shown herein below.

[0027] [ka]

[0028] The polymer is made from three phenylpropanoid monomer precursors:

[0029] [ka] Coumaryl Alcohol Coniferyl Alcohol Sinapyl Alcohol

[0030] which are the result of the enzyme-mediated dehydrogenative polymerization of the following components:

[0031] [ka] Hydroxyphenyl (H) Guaiacyl (G) Syringyl (S)

[0032] This results in:

[0033] Coniferyl alcohol occurs in all species and is the predominant monomer in coniferous (softwood) trees. Deciduous (hardwood) species contain up to 40% sinapyl alcohol units, while grasses and crops may also contain coumaryl alcohol units.

[0034] Lignin can be classified according to its raw biomass source into softwood and hardwood lignin.

[0035] Suitable starting raw biomass sources for obtaining the desired lignin fractions include essentially pure lignin, as well as any lignin, including kraft lignin, biomass-derived lignin, alkaline pulping lignin, soda process lignin, organosolv pulping lignin, enzymatic process lignin, steam explosion lignin, and any combination thereof.

[0036] By the expression "essentially pure lignin" it is to be understood as at least 80% pure lignin, preferably at least 90% pure lignin, more preferably at least 95% pure lignin, based on the untreated dry biomass, the remainder being extractives and carbohydrates such as hemicellulose, as well as inorganic matter.

[0037] By the expression "kraft lignin" it should be understood that the lignin is derived from kraft black liquor. Black liquor is an alkaline aqueous solution consisting of lignin residues, hemicelluloses, and inorganic chemicals used in the kraft pulping process. Black liquor from the pulping process contains components from different softwood and hardwood species in different proportions. Lignin can be separated from black liquor by different techniques including, for example, precipitation and filtration. Lignin usually starts to precipitate at a pH below 11-12. Different pH values ​​can be used to precipitate lignin fractions with different properties. These lignin fractions can be characterized by their molecular weight distribution, e.g. M w and M. n The precipitated lignin may differ from one another by its polydispersity, content of hemicellulose and extractives, and inorganic material. The precipitated lignin may be purified from inorganic impurities, hemicellulose, and wood extractives using an acidic wash step. Further purification may be achieved by filtration.

[0038] Alternatively, lignin is separated from the pure biomass. The separation process may begin by liquefying the biomass with strong alkali, followed by a neutralization process. After the alkali treatment, lignin can be precipitated in a similar manner as shown above.

[0039] Alternatively, the separation of lignin from the biomass includes a step of enzymatic treatment, which modifies the lignin to be extracted from the biomass.

[0040] Lignin isolated from pure biomass is essentially sulfur-free (less than 3% sulfur content) and therefore useful in further processing.

[0041] Preferably, the lignin so separated is also subjected to a depolymerization process with the aim of further reducing the weight average molecular weight of the fragments.

[0042] In some embodiments, the lignin so separated is also subjected to a depolymerization process for the purpose of further reducing the weight and number average molecular weight of the fragments.

[0043] Suitable depolymerization processes include base-catalyzed depolymerization, acid-catalyzed depolymerization, metal-catalyzed depolymerization, ionic liquid mediated depolymerization, and supercritical fluid mediated lignin depolymerization.

[0044] In a preferred embodiment, the lignin fraction is obtained by base-catalyzed depolymerization.

[0045] Preferably, said lignin fraction is obtained by subjecting the separated lignin to base-catalyzed depolymerization at a temperature below 300° C. and a pressure below 30 MPa.

[0046] The pH is set to between 11 and 14 by adding a base, such as NaOH, KOH, Ca(OH)2, LiOH, K2CO3, or mixtures thereof.

[0047] For the purposes of the present invention, the weight average molecular weight (M w ) is measured by size exclusion chromatography (or "SEC"). SEC uses a stagnant liquid present in the pores of the beads as the stationary phase and a flowing liquid as the mobile phase. The mobile phase is therefore able to flow between the beads and also in and out of the bead pores. The separation mechanism is based on the size of the polymer molecules in solution. Larger molecules will elute faster. Smaller molecules, which can fit into the many pores in the beads, will take longer to pass through the column and therefore exit the column slowly. To measure the molecular weight of the components of a polymer sample, a calibration must be performed with standard polymers of known molecular weight. Values ​​from unknown samples are then compared to the calibration graph. The retention time depends on the column material used, the eluent, and how similar the standards used are compared to the sample.

[0048] In the present invention, the eluent is preferably 0.1 M NaOH.

[0049] Preferably, the lignin fraction comprises fragments having a weight average molecular weight of up to 6,000 Daltons.

[0050] More preferably, the lignin fraction comprises fragments having a weight average molecular weight up to 5,500 Daltons.

[0051] Even more preferably, the lignin fraction comprises fragments having a weight average molecular weight of up to 5,000 Daltons.

[0052] In some embodiments, the lignin fraction comprises fragments having a weight average molecular weight up to 2,000 Daltons.

[0053] In a preferred embodiment, the lignin fraction comprises fragments having a weight average molecular weight up to 1,500 Daltons.

[0054] In another embodiment, the lignin fraction comprises fragments having a weight average molecular weight of 150 Daltons or greater.

[0055] In a preferred embodiment, the lignin fraction comprises fragments having a weight average molecular weight of from 150 Daltons to 6,000 Daltons, preferably having a weight average molecular weight of from 250 Daltons to 5,000 Daltons, and more preferably having a weight average molecular weight of from 500 Daltons to 2,500 Daltons.

[0056] Preferably in these embodiments, the fragments contain, on average, up to 30 phenylpropane units, more preferably, on average, up to 27 phenylpropane units.

[0057] The molecular weights of the three phenylpropanoid monomer precursors vary between 150 Da for coumaryl alcohol, 180 Da for coniferyl alcohol, and 210 Da for sinapyl alcohol. The average weight is therefore 180 Da, and this value has been used as the "phenylpropane unit". wThe value was divided by 180 Da to obtain the weight average number of phenylpropane units.

[0058] In another embodiment, the lignin fraction has a number average molecular weight (M) of up to 2,000 Daltons. n )

[0059] For the purposes of the present invention, the number average molecular weight (M n ) is measured by size exclusion chromatography.

[0060] Preferably, the lignin fraction has a number average molecular weight (M) of up to 1,500 Daltons. n )

[0061] In a preferred embodiment, the lignin fraction comprises fragments having a number average molecular weight of 150 Daltons to 1,300 Daltons.

[0062] Without wishing to be bound by any theory, it is believed that a lower number average molecular weight means a more active molecule. This is proposed by considering that lower molecular weight means smaller fragments, and smaller fragments mean less cross-linked / shorter fragments, and less cross-linked / shorter fragments mean more free functional groups thereon, and therefore more reactive fragments.

[0063] Furthermore, it is believed that smaller molecules will more easily diffuse through and into the cell membrane of plant pathogens, thus significantly increasing the overall effectiveness of the lignin fraction.

[0064] Preferably in these embodiments, the fragments contain a number average of up to 11 phenylpropane units, more preferably a number average of up to 8 phenylpropane units.

[0065] The molecular weights of the three phenylpropanoid monomer precursors vary between 150 Da for coumaryl alcohol, 180 Da for coniferyl alcohol, and 210 Da for sinapyl alcohol. The average weight is therefore 180 Da, and this value has been used as the "phenylpropane unit". w The value was divided by 180 Da to obtain the number average number of phenylpropane units.

[0066] In a preferred embodiment, the lignin fraction has a weight average molecular weight (M) of 150 Daltons to 2,500 Daltons. w ), and fragments having number average molecular weights (M) up to 2,000 Daltons. n )

[0067] More preferably, the lignin fraction has a weight average molecular weight (M) of 150 Daltons to 2,500 Daltons. w ) and fragments having a weight average of 2 to 13 phenylpropane units and a number average molecular weight (M) of up to 2,000 Daltons. n ) and fragments having up to 11 phenylpropane units on a number average.

[0068] In a further embodiment, the lignin fraction has a polydispersity index (PDI) of 1.25 to 6.

[0069] Polydispersity Index (PDI) or heterogeneity index, or simply dispersity, is a measure of the distribution of molecular masses in a given polymer sample. PDI is a function of the weight average molecular weight (M w ) to the number average molecular weight (M n ) which gives the distribution of individual molecular masses within a batch of polymer.

[0070] In a particularly preferred embodiment, the lignin fraction has a weight average molecular weight (M w) and fragments having a weight average of 2 to 13 phenylpropane units, and wherein the lignin fraction has a polydispersity index of 1.25 to 6.

[0071] Particularly preferred embodiments also include those in which the lignin fraction has a number average molecular weight (M n ) and fragments having a number average of up to 11 phenylpropane units, and wherein the lignin fraction has a polydispersity index of 1.25 to 6.

[0072] In a most preferred embodiment, the lignin fraction has a weight average molecular weight (M) of 150 Daltons to 2,500 Daltons. w ) and a weight average of 2 to 13 phenylpropane units, with a number average molecular weight (M) of up to 2,000 Daltons n ) and fragments having a number average of up to 11 phenylpropane units, and wherein the lignin fraction has a polydispersity index of 1.25 to 6.

[0073] In a particularly preferred embodiment of the invention, the lignin fraction has a weight average molecular weight (M w ) and a weight average of 24-28 phenylpropane units, with a number average molecular weight (M n ) and fragments with a number average of 6-7 phenylpropane units.

[0074] In another particularly preferred embodiment of the invention, the lignin fraction has a weight average molecular weight (M w ) and a weight average of 4-8 phenylpropane units, with a number average molecular weight (M n) and fragments having a number average of 2-4 phenylpropane units. In these particularly preferred embodiments, the most abundant phenylpropane units in the lignin fraction are derived from coniferyl alcohol, while the less abundant phenylpropane units are derived from sinapyl alcohol.

[0075] The organic-inorganic hybrid material of the present invention preferably comprises a metal compound and a lignin fraction, wherein: the metal compound is selected from metal hydroxides, metal oxides, metal halides, metal sulfates, metal nitrates, metal gluconates, metal acetates, metal carbonates, metal oxychlorides, and combinations thereof, and the metal is selected from Mg, Ca, Ti, Fe, Mn, Co, Ni, Cu, Zn, Ag, Al, and mixtures thereof; - the lignin fraction has a weight average molecular weight (M) of 4,400 to 6,000 daltons w ) and a weight average of 24-33 phenylpropane units, with a number average molecular weight (M n ) and fragments having a number average of 6-7 phenylpropane units, and wherein the metal compound is embedded in the lignin fraction in an amount of up to 50 wt % based on the weight of the organic-inorganic hybrid material.

[0076] Alternatively, the organic-inorganic hybrid material of the present invention preferably comprises said metal compound and said lignin fraction, wherein: the metal compound is selected from metal hydroxides, metal oxides, metal halides, metal sulfates, metal nitrates, metal gluconates, metal acetates, metal carbonates, metal oxychlorides, and combinations thereof, and the metal is selected from Mg, Ca, Ti, Fe, Mn, Co, Ni, Cu, Zn, Ag, Al, and mixtures thereof; - the lignin fraction has a weight average molecular weight (M w) and a weight average of 4-8 phenylpropane units, with a number average molecular weight (M n ) and fragments having, on average, 2-4 phenylpropane units, and wherein the metal is embedded in the lignin fraction in an amount of up to 50 wt %, based on the weight of the organic-inorganic hybrid material.

[0077] More preferably, in the organic-inorganic hybrid material of the present invention, the metal compound is embedded in the lignin fraction in an amount of up to 40 wt %, based on the weight of the organic-inorganic hybrid material.

[0078] Particularly preferred is an organic-inorganic hybrid material comprising said metal compound and said lignin fraction, wherein: the metal compound is selected from brochanite, gerhardite, goethite, lepidocrocite, or mixtures thereof; - the lignin fraction has a weight average molecular weight (M w ), said fragments containing up to 30 phenylpropane units by weight average and having a number average molecular weight (M) of up to 2000 Daltons. n ), said fragment having a number average of up to 11 phenylpropane units; And wherein the metal is embedded in the lignin fraction in an amount of up to 40 wt %, based on the weight of the organic-inorganic hybrid material.

[0079] In another embodiment, the organic-inorganic hybrid material consists essentially of the metal compound and the lignin fraction as described above. For the purposes of the present invention, the term "consists essentially of" means that said metal compound and said lignin fraction are the only active components against harmful and pathogenic microorganisms present in the organic-inorganic hybrid material, with other possible components being impurities or unreacted starting materials.

[0080] In a further embodiment, the organic-inorganic hybrid material consists of a metal compound and a lignin fraction, as described above.

[0081] In another aspect, the present invention relates to a process for preparing said organic-inorganic hybrid material.

[0082] In a first embodiment, a process for preparing an organic-inorganic hybrid material comprises: i) providing an aqueous solution of a metal compound; ii) adding the lignin fraction and mixing for at least 1 hour; iii) adjusting the pH to 7-8 by addition of base; and iv) recovering and drying the resulting organic-inorganic hybrid material; The process includes the steps of:

[0083] In step ii) the lignin fraction is preferably added in a weight ratio to the metal of up to 5:1.

[0084] In step ii), the mixing is preferably carried out at room temperature for a period of 6-24 hours.

[0085] In another embodiment, in step ii), the mixing is carried out at room temperature for 1-3 hours, more preferably for about 2 hours.

[0086] In step iii), the base may be any inorganic base, such as NH3 or ammonium salts, oxides or hydroxides of Li, Na, K, Mg, Ca, Ba, Al, or mixtures thereof. Preferably, the base is Na hydroxide.

[0087] In step iv), the recovery is preferably carried out by filtering off the solid phase containing the obtained organic-inorganic hybrid material and drying at 70-80°C.

[0088] Optionally, the filtered solid phase can be washed with water before being dried. This can be done in order to remove the resulting salt of the base, however, if the resulting salt is not harmful but is instead a useful component, it is preferred not to wash the filtered solid phase. For example, if the starting metal compound is Cu sulfide and the base is Na hydroxide, the resulting salt is simply Na2SO4.

[0089] In a second embodiment, a process for preparing an organic-inorganic hybrid material comprises: a) providing said metal compound and said lignin fraction in powdered and dried form; b) adding a base, thus obtaining a solid mixture; c) grinding the solid mixture in a planetary ball mill; and d) collecting the resulting organic-inorganic hybrid material; The process includes the steps of:

[0090] It should be noted that in these second embodiments, no solvent is present and the process is carried out on ingredients that are entirely solid and dry.

[0091] The base in step b) may be the same as the base in step iii) above, but is preferably in solid form.

[0092] The above process makes it possible to obtain the organic-inorganic hybrid material of the invention, in which the lignin fraction and the metal components are intimately mixed.

[0093] For example, when the starting metal compound is Cu sulfide and the base is Na hydroxide, the resulting products are Na2SO4 and a hybrid material containing an intimate mixture of a lignin fraction and the basic salt of Cu, i.e., Cu2(SO4)(OH)6.

[0094] It should be understood that when the metal in the starting metal compound is Cu, both processes make it possible to obtain organic-inorganic hybrid materials, including brochante, as will be seen in the examples below.

[0095] The organic-inorganic hybrid material of the present invention has unexpectedly and surprisingly proven to be highly selective and effective as an antimicrobial agent against harmful and pathogenic microorganisms.Therefore, in another aspect, the present invention relates to the use of said organic-inorganic hybrid material as an antimicrobial agent in agriculture and in human and animal food.

[0096] For the purposes of the present invention, harmful and pathogenic microorganisms include both food pathogens and plant pathogens.

[0097] Food pathogens are gram-positive and gram-negative bacteria, and fungi, such as Escherichia coli, Candida albicans, Pseudomonas aeruginosa, Staphylococcus aureus, Salmonella enterditis, Campylobacter jejuni, and Listeria monocytogenes.

[0098] By the term "plant pathogen" is meant a parasitic organism on a plant host that thus causes a soil-borne or infectious disease, said organism being a bacterium, a fungus, an oomycete, or a virus.

[0099] Typical pathogenic bacteria are Erwinia amylovora, Pseudomonas syringae, Xanthomonas arboricola, and Xanthomonas campestris. Typical pathogenic fungi include Botrytis cinerea, Cercospora beticola, Zymoseptoria tritici, Fusarium solani, Alternaria solani, Rhizoctonia solani, Monilia laxa, Anthracnose of turfgrass, Apple powdery mildew, Apple scab, Black knot, Black sigatoka, Blackleg of oilseed rape, Brown rot of stone fruits, Dollar spot of turfgrass. of turfgrass, Dutch elm disease, Early blight of potato and tomato, Ergot of rye, Fusarium head blight, Fusarium wilt of watermelon and other cucurbits, Leucostoma canker of stone fruits, Monosporascus root rot, Mummy Berry, Rice blast, Septoria tritici blotch (STB) of wheat, Sudden death syndrome of soybean, Take-all root rot, Tan spot of cereals cereals), Verticillium wilt, White mold (Sclerotinia), Armillaria rootdisease, shoestring root rot, brown root rot, coffee rust, common smut of corn, daylily rust, Rhyzoctonia diseases of turfgrass, southern blight, southern stem blight, white mold, soybean rust, stem rust of wheat, stinking smut of wheat, wheat stem rust, and white pine blister rust. Typical pathogenic oomycetes include Phytophthora infestans, Plasmopara viticola, Aphanomyces root rot or common root rot of legumes, Black shank of tobacco, Downy mildew of cucurbits, Downy mildew of grape, Late blight of potato and tomato, Phytophthora blight of curcurbits, Phytophthora root and stem rot of soybean, Pythium blight of turfgrass, Sudden oak death, and others. death, ramorum blight, taro leaf blight, rapid blight of turfgrass, and Typical viruses include viroids and virus-like organisms. Most plant viruses have a small single-stranded RNA genome. However, some plant viruses also have double-stranded RNA or single- or double-stranded DNA genomes. These genomes may code for as few as three or four proteins: a replicase, a coat protein, a movement protein to allow cell-to-cell movement through the plasmodesmata, and sometimes a protein that allows propagation by a vector. Plant viruses have several more proteins and can use many different molecular translation methods.

[0100] Plant viruses are generally transmitted from plant to plant by vectors, but mechanical and seed transmission also occurs. Vector transmission is often by insects (e.g., aphids), but several fungi, nematodes, and protozoans have been shown to be virus vectors.

[0101] In many cases, the insects and viruses are specific for virus transmission, such as the sugar beet leafhopper, which transmits the curly top virus that causes disease in several crops.

[0102] This advantageously allows the organic-inorganic hybrid materials of the present invention to replace antibiotic treatment. Antibiotic resistance, defined as the emergence (and spread) of factors of bacterial resistance to antibiotics, is triggered by selective pressure exerted on microbial populations by excessive and / or inappropriate use of antibiotics. Organic-inorganic hybrid materials as described herein have proven to be effective alternatives to antibiotics for preventing and treating antibiotic-resistant infections.

[0103] As can be seen from the examples presented below, the organic-inorganic hybrid materials of the present invention advantageously and surprisingly exhibit significant antimicrobial properties that can improve the overall health and wellness of humans and animals, as well as the overall health of plants and crops.

[0104] In a further aspect, the present invention relates to an agrochemical product comprising an organic-inorganic hybrid material and an agrochemical additive.

[0105] Suitable additives are pH adjusters, acidity adjusters, water hardness adjusters, mineral oils, vegetable oils, chemical fertilizers, foliar fertilizers, and combinations thereof.

[0106] Representative additives include 2-ethylhexanol EO-PO, alkoxylated alcohols, alkoxylated fatty amines, alkoxylated triglycerides, alkyl polyglycosides, sodium alkyl ether sulfates, alkylphenol ethylene oxide condensates, alkylphenyl hydroxypolyoxyethylenes, allyl polyethylene glycol methyl ethers, amphoteric dipropionate surfactants, di-1-p-menthene, dimethylpolysiloxanes, esterified vegetable oils, ethylene oxide condensates, fatty acid esters, fatty alcohol ethylene oxide condensates, fatty alcohol polyalkoxylates, lecithin (large) bean), methylated rapeseed oil, n-dodecylpyrrolidone, n-methylpyrrolidone, n-octylpyrrolidone, nonionic surfactants, nonylphenol ethylene oxide condensates, paraffin oil, poly(vinylpyrrolidone / 1-hexadecene), polyacrylamide, polyalkylene glycols, polyalkylene oxides, polyether modified trisiloxanes, polyethylene polypropylene glycols, polyoxyethylene monolaurate, propionic acid, styrene-butadiene copolymers, synthetic latex, tallow amine ethoxylates, vegetable oils, and mixtures thereof.

[0107] In view of the fact that the organic-inorganic hybrid material is effective even at very low concentrations, the agrochemical product advantageously and preferably comprises said organic-inorganic hybrid material in an amount such that it has a metal concentration of 5-200 grams per liter of agrochemical product.

[0108] The agricultural chemicals may be in solid or liquid form.

[0109] When the agrochemical is in a solid form, said solid form may be a tablet, minitablet, microtablet, granule, microgranule, pellet, mullite, micronized particle, or powder.

[0110] When the agrochemical product is in liquid form, the liquid form may be a solution, suspension, emulsion, dispersion, drops, or sprayable liquid, and may be a water- or oil-based liquid form. The liquid may include a solvent. Suitable solvents are water, glycols, alcohols, polyhydric alcohols, organic acids, and combinations thereof.

[0111] Preferred solvents are water, methanol, ethanol, n-propanol, iso-propanol, n-butanol, isobutanol, allyl alcohol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-ethylene glycol, polyethylene glycol (PEG), glycerol, lactic acid, polylactic acid, and mixtures thereof. More preferred solvents are water, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-ethylene glycol, polyethylene glycol (PEG), and mixtures thereof.

[0112] Preferably, when the agrochemical is in liquid form, said liquid form has a pH of 5-9, more preferably 6-8.

[0113] When the agrochemical product is in liquid form, said liquid form contains 1-50 wt% of the organic-inorganic hybrid material, which means that the agrochemical product can be diluted appropriately or directly mixed with other chemicals prior to use if desired.

[0114] The agrochemical products are granular bait, aerosol can, liquid (undiluted), bulk bait, matrix, concentrated bait, oil miscible liquid concentrate, encapsulated granule, capsule suspension, dispersible concentrate, powder, powder for dry tanning of seeds, emulsion, electrostatic liquid, water in oil emulsion, emulsion for tanning of seeds, oil in water emulsion, smokey jar, granule, smokey candle, smokey cartridge, smokey slat, concentrated suspension for tanning, smokey tablet, fumigant, smokey granule, (or pellet), gas (under pressure), granular bait, gasification product, fine powder, sliding powder, granular, oil based paste, hot smoke smoke concentrate, solid / liquid combination packaging, liquid / liquid combi packaging. The composition may be in the form of a combination packaging, cold smoke smoke concentrate, solid / solid combination packaging, lacquer, solution for seed tanning, microemulsion, microgranule, dispersible oil, oil miscible concentrated suspension, oil miscible liquid, oil suspension, paste, flat bait, concentrated paste or gel, pour-on, stick for plant, treated or coated seed, ready to use bait, spot-on, fragmented bait, concentrated suspension, suspension-emulsion, water soluble granule, soluble concentrate, film forming oil, water soluble powder, soluble powder for seed tanning, suspension, tablet, technical product, technical concentrate, powder for trace, liquid for trace, water dispersible microgranule, water dispersible granule, wettable powder, wettable powder for seed tanning, self-adhesive patch, and mixtures thereof.

[0115] Agrochemicals are produced using the following methods: - Mixing the agrochemical products with the seeds in the hopper of the seed drill; - Applying agrochemical products next to the seed furrows; - Applying agricultural chemicals to the entire field before or after soil tillage The method may be applied by one or more of the following:

[0116] If the agrochemical product is in liquid form, it may also be: - spraying tubers, bulbs and seeds with agrochemicals; - spraying agrochemical products onto the above-ground parts, leaves and stems of plants; - Immersing the plant roots in an aqueous solution containing agricultural chemicals It may also be applied by one or more of the following:

[0117] Depending on the final purpose of use, the agrochemical products are applied in amounts to achieve 100g-1000kg per hectare (ha), preferably 100g-100kg per ha, more preferably 100g-1000g per ha of organic-inorganic hybrid material. This means that the corresponding amount of metal used is surprisingly low. In fact, as can be seen in the examples below, highly significant results were observed for strawberry and tomato cultivation when 3 L / ha (i.e. 300g / ha) of organic-inorganic hybrid material containing 10% Cu was applied.

[0118] In a further aspect, the present invention relates to a food product comprising the organic-inorganic hybrid material and a suitable food ingredient.

[0119] The term "food product" means any edible product intended for both human and animal nutrition, including flour, bakery products (baked goods), animal feed, nutritional drinks, diet bars, edible oils, so-called "breakfast cereals", yogurt, fresh and dried pasta, ice cream, fruit juices or nectar, and confectioneries.

[0120] Preferably, when the food product is in liquid form, said liquid form has a pH of 2-14, more preferably 5-10, even more preferably 8-11.

[0121] In view of the fact that organic-inorganic hybrid materials are effective even at very low concentrations, food products advantageously and preferably contain said organic-inorganic hybrid materials in very reduced amounts. In a preferred embodiment of the food product, especially in animal food products, the organic-inorganic hybrid material is in an amount of up to 10 kg per ton of food product, more preferably 1-5 kg ​​per ton of food product.

[0122] In another aspect, the present invention relates to a food supplement comprising the organic-inorganic hybrid material and a suitable food carrier.

[0123] Food supplements may be in solid or liquid form.

[0124] When the dietary supplement is in a solid form, said solid form may be a tablet, minitablet, microtablet, granule, microgranule, pellet, multiparticulate, micronized particle, or powder.

[0125] When food supplement is in liquid form, said liquid form can be solution, suspension, emulsion, dispersion, droplet or sprayable liquid, and can be water- or oil-based liquid form.Said liquid form can contain solvent.Suitable solvents are water, glycol, alcohol, polyhydric alcohol, organic acid, oil, fat, and combinations thereof.

[0126] Preferred solvents are water, methanol, ethanol, n-propanol, iso-propanol, n-butanol, isobutanol, allyl alcohol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-ethylene glycol, polyethylene glycol (PEG), glycerol, lactic acid, polylactic acid, and mixtures thereof. More preferred solvents are water, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-ethylene glycol, polyethylene glycol (PEG), and mixtures thereof.

[0127] When the food supplement is in liquid form, the liquid form contains 5-70 wt% of the organic-inorganic hybrid material, which means that the food supplement is a concentrate and can be appropriately diluted or directly mixed with other carriers / ingredients prior to use, if desired.

[0128] In view of the fact that organic-inorganic hybrid material is effective even at very low concentrations, food supplements advantageously and preferably contain said organic-inorganic hybrid material in very reduced amounts.In a preferred embodiment of food supplements, especially food supplements for animals, organic-inorganic hybrid material is in an amount of up to 10 kg per tonne of food supplement, preferably 1-5 kg ​​per tonne of food supplement.

[0129] Suitable carriers are acidifiers, acidity regulators, anti-caking agents, antioxidants, fillers, resist agents, gelling agents, coating agents, modified starches, sequestering agents, thickeners, sweeteners, solvents, vehicles, dissociation agents, flow promoters, dyes, binders, lubricants, stabilizers, adsorbents, preservatives, wetting agents, flavorings, film formers, emulsifiers, wetting agents, release retarders, and mixtures thereof.

[0130] Preferably, the present invention relates to a food supplement for use as an antimicrobial agent in livestock feed.

[0131] In the present invention, the term "livestock" is meant to include both ruminant and non-ruminant animals. Ruminant animals are herbivorous animals with four-chambered stomachs that digest otherwise indigestible plant matter by fermenting it in their complex stomachs and ruminating it (they spit out a ball of semi-digested plant matter and then chew it again to destroy it before swallowing it again). They include cattle, sheep, goats, deer, antelope, giraffes, and camels, as well as their relatives, such as bison, musk oxen, okapi, and llamas. Non-ruminant animals, including pseudo-ruminants, can be pigs, horses, chickens, rabbits, turkeys, ducks, geese, quails, pheasants, partridges, and fish and shellfish. This means that the food supplement of the present invention can also be advantageously used in feeding fish and shellfish, i.e. in aquaculture.

[0132] Preferably, the present invention relates to a food supplement for use as an antimicrobial agent in pet foods, including dog foods, cat foods, bird foods, and fish foods.

[0133] In another preferred embodiment, the food supplement further comprises at least one resin acid, preferably abietic acid, dehydroabietic acid, palustric acid, neoabietic acid, pimaric acid, isopimaric acid, sandaropimaric acid, or esters thereof, or ethers thereof, or alkali or alkaline earth salts thereof, or mixtures thereof.

[0134] Preferably, the food supplement comprises up to 10 wt.%, more preferably up to 7 wt.%, of said at least one resin acid, based on the weight of the food supplement.

[0135] Resin acids are present in conifers and there are three main resin acid products: Tall Oil Rosin (TOR), Wood Rosin, and Gum Rosin. TOR is the resin acid fraction separated by vacuum distillation from Crude Tall Oil (CTO) produced by pulp preparation. CTO is obtained by acidification of Crude Tall Oil Soap or Crude Sulphate Soap (TOS). TOS is separated from cooking liquor, often called black liquor, in pulp mills during the pulping process. Wood rosin is the fraction separated by steam distillation or other means from dead wood, stumps, branches, etc., and GUM rosin is the resin fraction steam distilled or separated by other means from resin harvested from living trees, often called drilling.

[0136] Materials containing resin acids and obtained by vacuum distillation from crude tall oil include Distilled Tall Oil (DTO), Tall Oil Fatty Acid (TOFA), and Tall Oil Pitch (TOP). DTO contains 10-40% resin acids. CTO usually contains 15-70% resin acids, and the lowest resin acid content is generally provided by cooking mixed wood pulp.

[0137] The term "tall oil rosin" or "TOR" should be understood to refer to a composition obtained by distillation of crude tall oil and further refining of the distilled tall oil. TOR typically contains 60-99% (w / w) resin acids.

[0138] The term "wood rosin" should be understood to refer to a composition obtained by steam distillation or other means from dead trees, stumps, branches, etc. Wood rosin typically contains 50-99% (w / w) resin acids.

[0139] The term "GUM rosin" should be understood to refer to a composition obtained by distillation or separated by other means from resin harvested from living trees. GUM rosin typically contains 50-99% (w / w) resin acids.

[0140] The term "distilled tall oil" or "DTO" should be understood to refer to a composition obtained by distillation of crude tall oil and further refining of the distilled tall oil. DTO typically contains 10-60% (w / w) resin acids.

[0141] The resin acid based compositions TOR, wood rosin, GUM rosin, CTO, TOS, and DTO can also be prepared by mixing one or more resin acid compositions with one or more fatty acid compositions in the form of an oil or fat. The resin acid derivatives prepared are, for example, esters, ethers, or alkali metal salts.

[0142] Resin acids exhibit many properties, such as antibacterial, anti-inflammatory, antioxidant, and antibacterial biofilm properties. However, resin acids, especially in solid form, lack stability over time where they are subject to oxidation, spontaneous combustion, and packing.

[0143] Surprisingly, when at least one resin acid is mixed with the organic-inorganic hybrid material of the present invention, the resulting mixture, whether solid or liquid, is found to be very stable over time and free from oxidation, and therefore can fully benefit from the properties of the resin acid. This means that in the resulting food supplement containing the organic-inorganic hybrid material of the present invention, not only are the resin acids protected from degradation, but also a synergistic anti-inflammatory and antimicrobial effect is found between the lignin fraction and the resin acids.

[0144] The dietary supplement also contains at least one fatty acid, C 12 -C 24The composition may additionally contain an alkali or alkaline earth salt of, at least one biological oil, or a mixture thereof, which allows for better solubilization of the resin acids if a liquid form of the food supplement is preferred.

[0145] Preferably, the alkali or alkaline earth salt is a lithium, sodium, potassium, magnesium, calcium salt, or mixtures thereof.

[0146] Preferably, the fatty acid C 12 -C 24 They are lauric acid (C12), tridecylic acid (C13), myristic acid (C14), pentadecylic acid (C15), palmitic acid (C16), margaric acid (C17), stearic acid (C18), oleic acid (C18:1), linoleic acid (C18:2), alpha-linolenic acid (C18:3), gamma-linolenic acid (C18:3), nonadecylic acid (C19), arachidic acid (C20), heneicosanoic acid (C21), behenic acid (C22), tricosylic acid (C23), lignoceric acid (C24), stearic acid (C25), and oleic acid (C26). Lidonic acid (C18:4), eicosapentaenoic acid (C20:5), docosahexaenoic acid (C22:6), dihomo-gamma-linolenic acid (C20:3), arachidonic acid (C20:4), adrenic acid (C22:4), palmitoleic acid (C16:1), vaccenic acid (C18:1), paulic acid (C20:1), elaidic acid (trans-C18:1), gondoic acid (C20:1), erucic acid (C22:1), nervonic acid (C24:1), mead acid (20:3), or mixtures thereof.

[0147] In a preferred embodiment, the at least one fatty acid C 12 -C 24 The alkali or alkaline earth salt of is calcium palmitate, calcium laurate, calcium oleate, calcium soap of palm oil, or mixtures thereof.

[0148] The at least one biological oil comprises a fatty acid, anhydride or ester of a fatty acid, a triglyceride of a fatty acid, or a mixture thereof.Suitable biological oils are hemp oil, canola oil, sunflower oil, olive oil, corn oil, palm oil, coconut oil, pine oil, cottonseed oil, wheat germ oil, soya oil, safflower oil, linseed oil, tung oil, castor oil, soybean oil, peanut oil, rapeseed oil, sesame oil, rice germ oil, fish oil, whale oil, marine oil, or a mixture thereof.

[0149] Preferably, the food supplement comprises at least one fatty acid C 12 -C 24 of an alkali or alkaline earth salt, at least one fatty oil, or a mixture thereof, in a concentration of 1-100 kg per ton of food supplement.

[0150] It should also be understood that all combinations of the preferred embodiments of the organic-inorganic hybrid materials of the present invention, and of the food products, food supplements, processes, and uses thereof, as reported above, should be considered as disclosed herein.

[0151] All combinations of the preferred embodiments of the organic-inorganic hybrid material of the present invention, the food supplement, the process, and the respective uses disclosed above, should be understood to be disclosed herein.

[0152] The following are examples of the present invention, given for purposes of illustration. EXAMPLES

[0153] Mw and Mn in the examples were measured by size exclusion chromatography according to the following procedure.

[0154] "wt%" means weight percent based on the weight of the organic-inorganic hybrid material, unless otherwise specified.

[0155] Reagents and materials -Eluent: 0.1M NaOH, flow rate 0.5ml / min -Calibration for RI detector: Pullulan standard, M p : 100,000-1,080 (6 standards), in which M p is the peak maximum molecular weight -Calibration for UV detector (280 nm): PPS standard, polystyrene sulfonic acid sodium salt, M p 65,400-891 (6 standards). The standards are dissolved in ultrapure water to a concentration of approximately 5 mg / ml. The injection volume is 20 μl. -Quality control sample: known M w A lignin having a distribution is used.

[0156] Apparatus and Equipment -Dionex Ultimate 3000 autosampler, column compartment, and pump -Dionex Ultimate 3000 Diode Array Detector -Refractive index detector: Shodex RI-101 - Columns: PPS MCX column: precolumn and two analytical columns: 1000 Å and 100 000 Å, the column material is a sulfonated divinylbenzene copolymer matrix. -Syringe Filters Glass sample bottles for 0.45μm and standard (STD) samples. Sample Filtration: Mini-Uniprep Syringeless Filter Device PTFE or Nylon, 0.45μm. For prefiltration, 5μm syringe filters as needed. -Measuring bottle

[0157] procedure - Preparation of eluent Ideally, the water used to prepare the eluent should be high-quality deionized water with low resistivity (18 MΩ cm or less) containing as little dissolved carbon dioxide as possible. The water should be free of biological contaminants (e.g., bacteria and mold) and particulate matter. -Needle cleaning with 10% MeOH-water -Liquid samples Strongly alkaline liquid samples are diluted 1:100 and filtered into vials using a PTFE syringe filter (0,45 μm). Solid lignin samples are diluted and dissolved in 0.1 M NaOH and filtered through a PTFE, 0,45 μm syringe filter. The prepared samples are loaded into the autosampler. The injection volume is 20 μl. After the sample, 1 M NaOH is injected in the same way as the sample to clean the column. Equipment parameters: -Flow rate 0.5ml / min -Eluent 0.1M NaOH -Column oven temperature 30℃ -Isocratic run -Runtime: 48 minutes -Solid samples Dry the solid sample (lignin) overnight in a 60°C oven if necessary. Weigh out approximately 10 mg into a 10 ml weighing bottle. Dissolve and dilute the sample in 0.1 M NaOH solution and fill to the mark. Filter the sample through a PTFE, 0,45 μm filter. If the sample does not dissolve properly, it may be placed in an ultrasonic water bath or the sample may be filtered through a 5 μm syringe filter. -Standard samples for calibration Approximately 50 mg of each standard is weighed into a 10 ml weighing bottle and ultrapure water is added to fill to the mark. The standards are filtered using a PTFE 0.45 μm syringe filter. After the calibration sample run, the calibration results are collected and processed and stored using the processing method. The calibration is a linear first order calibration. -Quality control samples For lignin samples, known M w Lignin with the distribution is used as a quality control sample. The lignin is dissolved in 0.1 M NaOH at a concentration of approximately 1 mg / ml.

[0158] Example 1 Organosolv lignin obtained from beech wood (Fagus sylvatica (European beech)) was subjected to base-catalyzed depolymerization ("BCD"). The BCD process is carried out at 280°C and 250 bar, pH 12-14 for 8 minutes. The resulting lignin product consists of a liquid fraction and a solid fraction.

[0159] These fractions were then separated.

[0160] The liquid lignin fraction was an oil and had the following characteristics: Single species: Fagus sylvatica M w 100-300Da (1-2 phenylpropane units) Phenol 0% Guaiacol 15-20% Syringol 50-60% Catechol and methoxycatechol 5-10% Oligomers / Unknown 15-30%

[0161] The solid lignin fraction had the following characteristics: Single species: Fagus sylvatica M w 800-1,500 Da (4-8 phenylpropane units) M n 300-700Da (2-4 phenylpropane units) Structure of the OH-group: Aliphatic 0.2-0.4mmol / g Carboxylic acid 0.3-0.5mmol / g Condensed and syringyl types 1.0-2.0mmol / g Guaiacyl type 0.4mmol / g Catecholic and p-OH-phenyl 1.0-1.8mmol / g

[0162] This solid lignin fraction is referred to as "MMW" for short.

[0163] Example 2 The following lignin fractions have been extracted from kraft black liquor, said lignin fractions having the following characteristics: >95% of total solids Single species: Southern pine M w 4400-5000Da (24-28 phenylpropane units) M n 1200-1300Da (6-7 phenylpropane units) Structure of OH group: Aliphatic 2.1mmol / g Carboxylic acid 0.5mmol / g Condensed and syringyl forms 1.7mmol / g Guaiacyl type 2.0mmol / g Catecholic and p-OH-phenyl 4.0mmol / g

[0164] This solid lignin fraction is referred to as "HMW" for short.

[0165] Equipment used in the following examples: -Inductively Coupled Plasma (ICP) -X-ray powder diffraction analysis (XRPD) -Environmental Scanning Electron Microscope (ESEM) -Energy dispersive X-ray analysis (EDX) -Transmission Electron Microscope (TEM)

[0166] The copper content was determined by inductively coupled plasma atomic emission spectroscopy (ICP-AES) analysis. 100 mg of solid sample was suspended in 5 mL of HNO3 65% and 1 mL of H2O2 30%, then digested in a Milestone microwave MLS-1200 MEGA (digestion sequence: 1 min at 250 watts, 1 min at 0 watts, 5 min at 250 watts, 5 min at 400 watts, 5 min at 650 watts, 5 min cooling). The solution was diluted to 50 mL with double distilled water and analyzed by using an optical emission spectrometer JY2501, inductively coupled plasma in radial configuration HORIBA Jobin Yvon (Kyoto, Japan), ULTIMA2 model. Instrument features: Monochromator model JY2501; focal length 1m; resolution 5pm; nitrogen flow rate 2 l / min. ICP source: Meinhard type nebulizer, cyclonic spray chamber; argon flow rate 12 l / min; wavelength range 160-785nm; optical bench temperature 32°C. The wavelengths used for quantitative analysis were selected by examining emission lines of greater relative intensity, ensuring the absence of spectral interference with argon emission lines. Acquisition parameters: Wavelength Cu (nm): 224.700; Voltage (V): 580; Gain: 100. Quantitative analysis was performed after obtaining a calibration line using a standard solution at 10% in HNO3 to simulate the final acidity of the samples; the concentration range of the standards varied from 1mg / L to 100mg / L. Data acquisition and processing were performed with ICP JY v5.2 software (Jobin Yvon).

[0167] Infrared (IR) spectra were recorded using a Nicolet 5PC FT-IR spectrophotometer equipped with an ATR accessory in the range 4000-400 cm-1. An aliquot of the sample was ground in a mortar prior to data acquisition.

[0168] Powder X-ray diffraction (PXRD) analyses were carried out on a Thermo ARL X'tra diffractometer using Cu Kα radiation.

[0169] Electron diffraction experiments were performed using a Philips TECNAI F20 transmission electron microscope (TEM) operating at 200 kV. Samples were ground and suspended in isopropyl alcohol, then a few drops of the solution were evaporated onto copper or gold grids coated with an amorphous carbon film.

[0170] ESEM analysis was performed on a Quanta™ 250 FEG (FEI, Hillsboro, OR) equipped with an energy dispersive spectrometer (EDS) for X-ray microanalysis (Bruker Nano GmbH, Berlin, Germany) operating in low vacuum mode (70 Pa). The EDS has a QUANTAX XFlash® 6|30 detector with an energy resolution of ≦126 eV FWHM in Mn Kα.

[0171] Example 3 1 g of HMW from Example 2 was mixed with an aqueous solution of CuSO4·5H2O as shown in the table below:

[0172] [Table 1]

[0173] The pH was adjusted to 7-8 with dropwise addition of 1M NaOH. The mixture was stirred at room temperature for 24 hours, then the solid was filtered off, washed with water, and air-dried. The powder was oven-dried at 70-80°C; the weight loss was an average of 5%.

[0174] The resulting organic-inorganic hybrid material is: - Inductively Coupled Plasma (ICP) to measure metal content after microwave digestion of powders -X-ray powder diffraction analysis (XRPD) -Environmental Scanning Electron Microscope (ESEM) -Energy dispersive X-ray analysis (EDX) -Transmission Electron Microscope (TEM) was characterized by.

[0175] ICP analysis showed the following metal contents for each sample of the prepared organic-inorganic hybrid materials:

[0176] [Table 2]

[0177] XRPD and TEM analyses showed the presence of the same solitary copper-containing phase in all samples examined, regardless of the % of copper uploaded into the organic-inorganic hybrid material (Figure 1).

[0178] Comparison of the XRPD plots with a mineral database [Helliwell, M.; Smith, J. V. Brochantite. Acta crystallog. C, 1997, Vol. 53, P. 1369-1371] allowed the identification of the recurring mineral phase as brochantite, with the formula Cu4SO4(OH)6, embedded in a lignin matrix (Figure 2, showing matching overlap between HMW-Cu 42% and brochantite).

[0179] ESEM analysis was performed on samples containing various metal contents. As an example, in Figure 3, an image of a sample containing 17 wt% copper (HMW-Cu 17%) as brochanite is shown with scale units ranging from 20 μm to 10 μm.

[0180] EDX analysis confirmed the presence of copper; moving across the granule surface, the metal appears to be uniformly distributed over the entire granule. Figure 4 shows an EDX spectrum showing the results of in situ elemental analysis at one location on a granule of HMW-Cu 17%.

[0181] HMW-Cu samples with various copper contents were analyzed using TEM analysis. This technique makes it possible to obtain nanometric images and even generate in situ electron diffraction patterns. Images were collected in bright field and STEM (scanning transmission electron microscope) modes.

[0182] As an example, in FIG. 5 images are reported in both bright field and STEM modes for a sample containing 14% copper as brochanite (HMW-Cu 14%) as shown by ICP.

[0183] Small sticks (nanometer scale) are mixed with a granular lignin matrix. Diffraction patterns show that these sticks are small crystals of brochanite. The sticks are 25 nm wide (average).

[0184] TEM analysis was also performed on a sample containing 2% copper (HMW-Cu 2%) as measured by ICP. In this case, the image (Figure 6) shows the presence of nanometric spheres scattered on the granules. The spheres are about 10 nm in diameter and appear to consist of brochanite, as shown by the electron diffraction pattern collected in situ.

[0185] Metal release in water at different pH values. To study the metal release in water at different pH values, about 250 mg of HMW-Cu 18% was stirred in 25 mL of buffer at room temperature for 24 hours. The suspended solids were filtered off and the filtrate was collected and dried, after which the metal content was measured by ICP. The results are reported in the table below.

[0186] [Table 3]

[0187] Copper release at acidic pH is almost complete, whereas it is negligible at neutral pH or in distilled water (pH 6-6.5). These data suggest that in agricultural applications, soil pH can have a profound effect on the activity of the samples, and that controlled release can be obtained as a function of pH.

[0188] Example 4 1 g of MMW from Example 1 was mixed with an aqueous solution of CuSO4·5H2O as shown in the table below.

[0189] [Table 4]

[0190] The pH was adjusted to 7-8 with dropwise addition of 1M NaOH. The mixture was stirred at room temperature for 24 hours, then the solid was filtered off, washed with water, and air-dried. The powder was further oven-dried at 70-80°C; the weight loss was an average of 5%.

[0191] The resulting organic-inorganic hybrid material is: - Inductively Coupled Plasma (ICP) to measure metal content after microwave digestion of powders -X-ray powder diffraction analysis (XRPD) -Environmental Scanning Electron Microscope (ESEM) -Energy dispersive X-ray analysis (EDX) -Transmission Electron Microscope (TEM) was characterized by.

[0192] ICP analysis showed the following metal contents for each sample of the prepared organic-inorganic hybrid materials:

[0193] [Table 5]

[0194] XRPD and TEM analysis showed the presence of the same copper-containing phase alone in all samples examined, regardless of the % of copper uploaded in the organic-inorganic hybrid material. The crystalline phase is the same as that described in Example 3 (Figure 8). Comparison of the XRPD plots with a mineral database [Helliwell, M.; Smith, JV Brochantite. Acta crystallog. C, 1997, Vol. 53, p. 1369-1371] allowed the identification of the recurring mineral phase as Brochantite, with the formula Cu4SO4(OH)6, embedded in a lignin matrix.

[0195] ESEM analysis was performed on samples containing various metal contents. In FIG. 8, an image of a sample containing 18% copper (MMW-Cu 18%) as brochanite is shown with scale units ranging from 100 μm to 2 μm.

[0196] EDX analysis confirmed the presence of copper; moving across the granule surface, the metal appears to be distributed evenly over the entire granule. Figure 9 is an EDX spectrum showing the results of in situ elemental analysis at one location on a granule of MMW-Cu 18%.

[0197] TEM analysis was also performed on a sample containing 14% copper (MMW-Cu 14%) as measured by ICP.

[0198] High-resolution diffraction and phase contrast imaging (HREM), selected area electron diffraction techniques (SAED), and energy dispersive X-ray analysis (EDX) were used. In Figure 10, crystals of MMW-Cu 14% can be observed at the 20 nm scale. SAED analysis confirmed that the crystalline phase is brochanite.

[0199] In FIG. 11, a STEM image of brochantite crystals embedded in a MMW matrix (MMW-Cu 15%) is shown together with an X-ray microanalysis of a selected area.

[0200] In FIG. 12, brochantite crystals (white) are shown at 14% MMW-Cu.

[0201] Metal release in water at different pH values. To study the metal release in water at different pH values, about 250 mg of MMW-Cu 18% was stirred in 25 mL of buffer at room temperature for 24 hours. The suspended solids were filtered off and the filtrate was collected and dried, after which the metal content was measured by ICP. The results are reported in the table below.

[0202] [Table 6]

[0203] Copper release at acidic pH is almost complete, whereas it is negligible at neutral pH or in distilled water (pH 6-6.5). These data suggest that in agricultural applications, soil pH can have a great influence on the activity of the samples, and that controlled release can be obtained as a function of pH.

[0204] Example 5 1 g of HMW from Example 2 was mixed with an aqueous solution of Cu(NO3)2·3H2O as shown in the table below.

[0205] [Table 7]

[0206] The pH was adjusted to 7-8 with dropwise addition of 1M NaOH. The mixture was stirred at room temperature for 24 hours, then the solid was filtered off, washed with water, and air-dried. The powder was further oven-dried at 70-80°C; the weight loss was an average of 5%.

[0207] The resulting organic-inorganic hybrid material is: - Inductively Coupled Plasma (ICP) to measure metal content after microwave digestion of powders -X-ray powder diffraction analysis (XRPD) was characterized by.

[0208] ICP analysis showed the following metal contents for each sample of the prepared organic-inorganic hybrid materials:

[0209] [Table 8]

[0210] XRPD analysis showed the appearance of mineral phases and the same in samples prepared independent of lignin / salt ratio (Figure 13). Comparison of these XRPD plots with the mineral database [Helliwell, M.; Smith, J. V. Brochantite. Acta crystallog. C, 1997, Vol. 53, P. 1369-1371] allowed the identification of the emerging mineral phase as Gerhardite with formula Cu2(OH)3NO3.

[0211] Example 6A In view of the industrial scale-up of the sample preparation, a mechanochemical synthesis (solvent-free conditions) was performed: 1 g of HMW and 1.2 g of CuSO4·5H2O, in their powder form, were vigorously ground together in a planetary ball mill in the presence of NaOH (300 mg).

[0212] An agate grinding jar with balls of the same material was used. Samples were collected and washed with water to remove traces of unreacted salts. XRPD analysis of the resulting organic-inorganic hybrid material was performed, which showed the formation of Brochantite (Figure 14).

[0213] Example 6B In view of the industrial scale-up of the sample preparation, a mechanochemical synthesis (solvent-free conditions) was performed. 1 g of HMW and 1.2 g of CuSO4·5H2O were mixed in their powder form. They were vigorously ground together in a planetary ball mill in the presence of Ca(OH)2 (280 mg).

[0214] An agate grinding jar with balls of the same material was used. Samples were collected and washed with water to remove traces of unreacted salts. XRPD analysis of the resulting aggregates was performed, which showed the formation of brochantite and gypsum (CaSO4·2H2O).

[0215] Example 7 1 g of the MMW of Example 1 and 1.2 g of CuSO4·5H2O in their powder form were vigorously ground together in a planetary ball mill in the presence of NaOH (300 mg).

[0216] An agate grinding jar with balls of the same material was used. Samples were collected and washed with water to remove traces of unreacted salts. XRPD analysis of the samples was performed, which showed the formation of Brochantite (Figure 15).

[0217] Example 8 1 g of HMW from Example 2 was mixed with an aqueous solution of FeSO4·7H2O as shown in the table below.

[0218] [Table 9]

[0219] Two equivalents of 1M NaOH were slowly added dropwise. The mixture was stirred at room temperature for 24 hours, then the solid was filtered off, washed with water and air-dried; the powder was further oven-dried at 80° C. for 30 hours.

[0220] ICP analysis showed the following metal contents for each sample of the prepared organic-inorganic hybrid materials:

[0221] [Table 10]

[0222] XRPD showed the presence of crystalline phases, even though most samples showed low crystallinity (Figure 16).

[0223] Comparison of the XRPD plot with the mineral database [Helliwell, M.; Smith, J. V. Brochantite. Acta crystallog. C, 1997, 53, 1369-1371] led to the assumption that the mineral phase was FeO(OH), crystallized as a mixture of two polymorphs, namely goethite and lepidocrocite (Figure 17).

[0224] Metal release in water at different pH values. To study the metal release in water at different pH values, samples containing 20% ​​Fe (HMW-Fe 20%) were stirred in water or buffer for 2 hours at room temperature. The suspended solids were filtered off and the filtrate was collected and analyzed by ICP to determine the iron content. The results are reported in the table below. Interestingly, the uploaded iron appears to be stable at acidic and neutral pH.

[0225] [Table 11]

[0226] Example 9 1 g of HMW from Example 2 was mixed with an aqueous solution of CuSO4·5H2O as shown in the table below.

[0227] [Table 12]

[0228] The pH was adjusted to 7-8 with dropwise addition of 1M NaOH. The mixture was stirred at room temperature for 2 hours, then the solid was filtered off, washed with water and air-dried. The powder was oven-dried at 70-80°C.

[0229] The resulting organic-inorganic hybrid material is: - Inductively Coupled Plasma (ICP) to measure metal content after microwave digestion of powders -X-ray powder diffraction analysis (XRPD) -Transmission Electron Microscope (TEM) was characterized by.

[0230] ICP analysis showed the following metal contents:

[0231] [Table 13]

[0232] XRPD and TEM analysis showed the sole presence of the same copper-containing phase (Figures 18 and 19).

[0233] TEM analysis was used to analyze the sample of HMW-Cu 10% copper obtained at 2 hours. This technique makes it possible to obtain nanometric images and also to generate electron diffraction patterns in situ. Images were collected in bright field mode and in STEM (Scanning Transmission Electron Microscope) mode (Figure 19).

[0234] Referring to Figure 19, small sticks (nanometer scale) are mixed with the granular lignin matrix. The diffraction pattern shows that these sticks are small crystals of brochanite. The sticks are 20 nm wide (average) and have lengths in the range of 50 and 200 nm.

[0235] Example 10 620.35 mg of HMW was placed in an 80 ml agate grinding jar together with 310.2 mg of CuSO4·5H2O and 69.4 mg of Ca(OH)2. 1 ml of water was then added to the mixture. The water content corresponds to 50 wt% for the target material HMW-Cu. The reaction was carried out in a planetary ball mill with the aim of mechanochemically obtaining the hybrid material. The parameters used for the synthesis are summarized in the table below.

[0236] [Table 14]

[0237] The solid was filtered off, washed with water and air dried. The powder was oven dried at 70-80° C. overnight.

[0238] The resulting organic-inorganic hybrid material was characterized by X-ray powder diffraction analysis (XRPD), which confirmed the formation of the same copper-containing phase (Figure 20).

[0239] Example 11 antimicrobial activity The antimicrobial activity of the organic-inorganic hybrid materials of the present invention was evaluated by in vitro antimicrobial susceptibility testing using broth microdilution and agar dilution methods (CLSI protocols-Clinical and Laboratory Standards Institute). The aim was to quantitatively measure the in vitro activity of the organic-inorganic hybrid materials against a given isolated microorganism, thereby characterizing the minimum inhibitory concentration.

[0240] The agar dilution method was used: the organic-inorganic hybrid materials were incorporated in agar medium (specific for each microorganism) at various concentrations and, after solidification of the medium, the inoculum (104 CFU / ml for fungi and 105 CFU / ml for bacteria) was applied to the agar surface.

[0241] Broth microdilution assay: Organic-inorganic hybrid materials were diluted in specific liquid media in the presence of well-defined microbial suspensions (104 CFU / ml for fungi and 105 CFU / ml for bacteria).

[0242] In the broth microdilution assays, the organic-inorganic hybrid materials were diluted in a specific liquid medium, but they resulted in insolubility at the bottom of the well due to the formation of a precipitate, therefore MICs were primarily determined using the agar dilution assay.

[0243] The organic-inorganic hybrid materials investigated were: -Lignin - High Molecular Weight (HMW) -Lignin - Medium Molecular Weight (MMW) -Copper hydroxide - HMW-Cu with a copper content of 2.6% (w / w) (HMW-Cu 2) - HMW-Cu with a copper content of 5.6% (w / w) (HMW-Cu 6) -HMW with copper content of 10% (w / w) (HMW-Cu 10) -MMW with copper content 2.2% (w / w) (MMW-Cu 2) -MMW with copper content 4% (w / w) (MMW-Cu 4) -MMW with copper content of 9.3% (w / w) (MMW-Cu 9 It was.

[0244] MICs were determined for the following harmful and pathogenic microorganisms: Bacteria and fungi (basic and feed-related screening) Escherichia coli: Pseudomonas aeruginosa Staphylococcus aureus Salmonella enteriditis Campylobacter jejuni Candida albicans

[0245] Bacteria and fungi (specific screening in biocontrols): Erwinia amylovora, Kiwifruit canker pathogen (Pseudomonas syringae pv. actinidiae) Peach Bacterial Borre (Xanthomonas arboricola pv.pruni) Xanthomonas campestris Alternaria solani Botrytis cinerea Fusarium solani Rhizoctonia solani Monilia laxa Septoria tritici

[0246] The study included two controls: positive control activity through the use of miconazole (against fungi) and ceftriaxone (against bacteria).

[0247] All experiments were performed in triplicate and yielded very similar inhibition results.

[0248] The results are shown in the table below. In brackets is the copper concentration (g / l) relative to the corresponding copper-lignin derivative. For copper sulfate pentahydrate (copper) and copper hydroxide (copper 2), the MIC refers to the copper concentration (g / l).

[0249] [Table 15]

[0250] [Table 16]

[0251] Example 12 Field evaluation of the efficacy and selectivity of organic-inorganic hybrid material of example HMW-Cu 10 against Botrytis cinerea in strawberry under greenhouse conditions Test conditions:

[0252] [Table 17]

[0253] Crop information:

[0254] [Table 18]

[0255] Application schedule and product description:

[0256] [Table 19]

[0257] result Summary n.1 - Percentage of fruit infected and efficacy of treatment against Botrytis cinerea

[0258] [Table 20]

[0259] Abstract n.2 - Weight of attached and healthy fruits and percentage of attached fruits for treatments against Botrytis cinerea on May 28, 2018

[0260] [Table 21]

[0261] The results reported above show that the organic-inorganic hybrid material of the present invention is surprisingly able to act effectively against Botrytis cinerea while at the same time significantly reducing the overall amount of Cu, i.e. heavy metal, to be used.

[0262] Example 13 Field evaluation of the organic-inorganic hybrid material of Example HMW-Cu 10 for efficacy and selectivity against various bacteria and diseases of tomato in greenhouse Test conditions:

[0263] [Table 22]

[0264] Crop information:

[0265] [Table 23]

[0266] Application schedule and product description:

[0267] [Table 24]

[0268] result

[0269] [Table 25]

[0270] Sample HMW-Cu 10 was tested and compared with a commercial Cu-based product, namely Coprantol, to evaluate its efficacy in controlling bacterial infection caused by Rhizoctonia solani on greenhouse grown tomatoes.

[0271] The amounts of Cu examined were: Coplantol: 600g / ha HMW-Cu 10: 100g / ha HMW-Cu 10: 30 g / ha It was.

[0272] As clearly shown in FIG. 21, both studies with HMW-Cu 10 unexpectedly and surprisingly showed higher efficacy than Coplantol, despite the very low doses used, i.e., 6 and 20 times lower than the Coplantol dose.

Claims

1. 1. An organic-inorganic hybrid material consisting essentially of a metal compound and a lignin fraction, comprising: - the metal compounds include brochanite, gerhardite, goethite, lepidocrocite, or mixtures thereof; the lignin fraction comprises fragments having a weight average molecular weight of up to 10,000 as measured by size exclusion chromatography, the fragments comprising, on average, up to 55 phenylpropane units; the metal compound represents the inorganic material of the organic-inorganic hybrid material, and the lignin fraction represents the organic polymer of the organic-inorganic hybrid material; And wherein the metal compound is scaffolded on the lignin fraction in an amount of up to 50 wt % based on the weight of the organic-inorganic hybrid material.

2. 10. The hybrid material of claim 1, wherein the lignin fraction comprises fragments having a weight average molecular weight of from 150 to 6,000 as measured by size exclusion chromatography.

3. 3. The hybrid material of claim 1 or 2, wherein the lignin fraction comprises fragments having a number average molecular weight of up to 2,000 as measured by size exclusion chromatography.

4. The hybrid material comprises a metal compound and a lignin fraction, wherein: - the metal compounds include brochanite, gerhardite, goethite, lepidocrocite, or mixtures thereof; the lignin fraction comprises fragments having a weight average molecular weight of 4,400 to 6,000 and a weight average of 24-33 phenylpropane units, a number average molecular weight of 1,200 to 1,300 and a number average of 6-7 phenylpropane units, and wherein the metal compound is scaffolded on the lignin fraction in an amount of up to 50 wt % based on the weight of the organic-inorganic hybrid material; Or, The organic-inorganic hybrid material comprises the metal compound and the lignin fraction, wherein: - the metal compounds include brochanite, gerhardite, goethite, lepidocrocite, or mixtures thereof; the lignin fraction comprises fragments having a weight average molecular weight of 800 to 1,500 and a weight average of 4-8 phenylpropane units, a number average molecular weight of 300 to 700 and a number average of 2-4 phenylpropane units, 4. The hybrid material of claim 1, wherein the metal is scaffolded on the lignin fraction in an amount of up to 50 wt % based on the weight of the organic-inorganic hybrid material.

5. The hybrid material comprises the metal compound and the lignin fraction, wherein: the lignin fraction comprises fragments having a weight average molecular weight of 150 to 5,500, the fragments comprising up to 30 phenylpropane units by weight average, and fragments having a number average molecular weight of up to 2000, the fragments comprising up to 11 phenylpropane units by number average, 5. The hybrid material of claim 1, wherein the metal is scaffolded on the lignin fraction in an amount of up to 40 wt %, based on the weight of the organic-inorganic hybrid material.

6. 10. A process for preparing the organic-inorganic hybrid material of claim 1, comprising: i) providing an aqueous solution of a metal compound; ii) adding the lignin fraction and mixing for at least 1 hour; iii) adjusting the pH to 7-8 by addition of base; and iv) recovering and drying the resulting organic-inorganic hybrid material; or a) providing said metal compound and said lignin fraction in powdered and dried form; b) adding a base, thus obtaining a solid mixture; c) grinding the solid mixture in a planetary ball mill; and d) collecting the resulting organic-inorganic hybrid material; A process including the steps of:

7. Use of the organic-inorganic hybrid material according to any one of claims 1 to 5 as an antimicrobial agent in agriculture.

8. 6. An agricultural chemical product comprising the organic-inorganic hybrid material according to any one of claims 1 to 5 and an agricultural chemical additive.

9. 9. The agrochemical of claim 8, comprising said organic-inorganic hybrid material in an amount such that it has a metal concentration of 5-200 grams per liter of agrochemical.

10. Use of the organic-inorganic hybrid material according to any one of claims 1 to 5 as an antimicrobial agent in human and animal diet.

11. A food product comprising the organic-inorganic hybrid material according to any one of claims 1 to 5 and a suitable food ingredient.

12. A food supplement comprising the organic-inorganic hybrid material according to any one of claims 1 to 5 and a suitable food carrier.

13. 13. The food supplement of claim 12, further comprising at least one resin acid.

14. 14. A food supplement according to claim 13, comprising up to 10 wt% of said at least one resin acid, based on the weight of said food supplement.

15. At least one fatty acid C 12 -C 24 15. A food supplement according to any one of claims 12 to 14, further comprising an alkali or alkaline earth salt of, at least one fatty oil, or a mixture thereof.

16. The at least one fatty acid C 12 -C 24 16. The food supplement of claim 15, comprising an alkali or alkaline earth salt of at least one fatty oil, or a mixture thereof, in a concentration of 1-100 kg per tonne of food supplement.

17. 17. A food product according to claim 11, or a food supplement according to any one of claims 12 to 16, for use as an antimicrobial agent in livestock feed or pet food.

Citation Information

Patent Citations

  • Lignin / silver composite antibacterial agent, and preparation method and application thereof

    CN107312315A

  • Carcinogenesis promotion-inhibiting composition

    JP2006083077A

  • Rubber composition and molded body

    JP2016069513A

  • Food such as lonicera caerulea l. including medical ingredient with antimicrobial, anticancer or antiviral effect and showing drug activity when receiving patent and sold

    JP2016073296A

  • Method of producing copper hydoroxosulphates and copper fungicidal compositions containing same

    US20070003635A1